`It Will Always Be with Us': Corruption as an Ontological Fact among Kenyan Luo - Mario Schmidt (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2014)
Revolving around the gap between the emic judgement that corruption cannot be eliminated and the etic attempts to bring this elimination about, this paper looks at the ontological preconditions of Luo politics in western Kenya and the way in which these render both the objective measurement and the eradication of corruption impossible. By taking the statements of people on the ground seriously, the paper aims to expose the Eurocentric mind-set that lies at the heart of most discourses on corruption. Unless we expect the Luo to change the way in which they conceptualize sociality, our only course is to embrace corrupt behaviour—which goes to prove that cooperation is sometimes obliged to follow rather curious paths.
urn:nbn:de:hbz:464-20150105-111139-5
Keywords: 320; Cooperation; corruption; development aid; gift; Kenya; Luo